Antik Roma’da kadın - Ergene, Ayşegül (My University, 1998)
This thesis presents and explains social, cultural, daily and personal life of Roman women from the founding times of Rome to the end of the third century A.D. Unjust treatments with which Roman women were confronted are also particulary emphasized by talking about their kinds, limits and alteration in the development. The study is composed of two main chapters: Famous Roman women from the founding times of Rome to the end of the third century A.D. and Position of women in the Roman society. In the first chapter, famous women in the Roman history are researched individually as well as generally. In the second chapter, engagements, wedding feasts, reasons of lucky and unlucky matrimonies, divorces, divorced women, moral bankrupt and sacred women are treated under the titles Legal position of women in the Roman society and Traditional situation. In the same chapter, it's talked about labors, dresses, shoes, jewellery, hairdressings, make-ups, bathrooms of women as well as their education, music, dance and sport under the title Daily life of Roman women. As the result of these researches, it can be said for the emancipation of the Roman women that they had no political rights. In the Roman government were only the men. The position of the Roman women in the society was not however so tedious as we imagine. This is evident at their legal position, especially at the laws, which arranged the wardship of the women, and their large properties beginning from the early times. On the other hand, all these do not mean that the Roman women had the equal rights as the men, or that they were on this way. Comparing with the Greek women, we can see also that the Roman women were more intellectual and privileged persons, and that they could go with their husbands even to the meals.
Keywords: Kadınlar; Kadınlar-Roma İmparatorluğu; Sosyal guruplar; Toplum bilimleri